PAPILLARY ADENOCARCINOMA OF THE LUNG - Siti Aisyah; Lely Hartati; Amiruddin (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2023)
Background : Lung cancer is the most common cause of cancer deaths worldwide. Mortality and incidence rates are generally highest in high-income countries, especially the United States and European countries. In the United States, it is estimated that 234,030 people were diagnosed with lung cancer in 2018. Adenocarcinoma is the most dominant type of histological lung cancer, with the papillary adenocarcinoma subtype rarely encountered.Case Report : A case was reported from a 66-year-old male with slaid number B / 4903/19. On macroscopic examination from biopsy tissue appeared gray, springy, with a volume of ± 0.2 cc. On microscopic examination, a tumor mass shows form a papillary structure with fibrovascular core and a small portion of solid. Consists of tumour cells with pleomorphic nuclei, rough chromatin, some with intranuclear vacuole, pale cytoplasm and protruding nuclei. Mitotic was found. Stroma consists of fibrous connective tissue infiltrated by tumor cells and inflammation of lymphocyte cells. Dilated blood vessels and congestion. Areas of necrosis and lymphovascular invasion were seen.Discussion and Conclusions : Based on the histopathological picture, the patient is diagnosed with papillary adenocarcinoma of the lung with a classical histology picture that makes it easy to established the diagnosis. Prognose was poor.